PENGUJIAN TEGANGAN TEMBUS PADA ISOLASI RUBBER DALAM RENDAMAN MINYAK - Slamet Hani (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Insulation materials used to secure the power lines must be guaranteed in advance to endure, and perform as expecled. Insulation materials fatal failure in the operation of electric power, as it will cause the cessation of service.Those problems be a very interesting experiment, in this study will be carried out tests on the insulation tape made from rubber. Tests will be carried out in open air conditions and immersed in transformer oil. The testing focused on aspects of the thickness of the specimen.After testing that the test results of high voltage states, in the open air breakdown voltage greater because of the thickness affects the breakdown voltage. And when soaked breakdown voltage value decreases due to the ugly rubber chemical properties of oil resistance and solvent resistance.Insulating tape Scotch ™ 130C Linerless Rubber Splicing Tape 3M production has a breakdown voltage of 22 888 V in the open air with a thickness of 0.762 mm and 25 833 V transformer oil in a bath with a thickness of 0.762 mm for 20 minutes immersion.